Strategi Pengembangan Keterampilan Bertanya Guru Di Sekolah Dasar - Mohamad Yudiyanto; Laesti Nurishlah; Mochammad Ramdan Samadi; Fithri Meiliawati (STAI Al-Mas'udiyah, 2024)
Teachers' questioning skills play a pivotal role in effective learning, particularly in elementary school settings. Effective questioning fosters a dynamic classroom environment, fostering active student engagement and enhancing learning outcomes. Through qualitative methods and a literature study model, this research underscores the significance of teachers' questioning skills in shaping meaningful learning experiences and empowering students in their educational journey. Utilizing appropriate questioning techniques not only promotes student involvement but also facilitates deeper comprehension through discussions, reflections, and problem-solving activities. This study emphasizes the critical role of teachers in orchestrating interactive learning environments that stimulate curiosity, critical thinking, and active participation among students.